Relações dialógicas em capítulos do livro didático: “Português Linguagens” - Santos, Eduardo Pereira (2015)
The aim of this paper is to analyze how are the dialogical relations in the enunciation of three chapters called "Diálogos", one of each volume of the textbook "Português Linguagens: Literatura, Produção de Texto e Gramática", applied to High School, written by William Roberto Cereja and Thereza Cochar Magalhães, in order to examine whether the proposed activities of these chapters are based on Bakhtin's thoughts about enunciation, discursive genre, and dialogism, as well as to verify if such exercises can promote student's understanding and learning about the covered content, according to the Parâmetros Curriculares Nacionais do Ensino Médio (2000). This textbook was chosen for having been adopted in several public schools in the past three years. In order to achieve the proposed aim, it is used the reflections on Bakhtin (2006, 2011), and the studies of Brait (2005, 2012), Faraco (2009), Fiorin (2008), Grillo (2005), Machado (2005), Marcuschi (2008), Marchezan (2005), Stam (1992, 2008), Sobral (2009), among others. Analyses evidenced that the proposals of the textbook in question are not based on Bakhtin's thought on dialogic relations, enunciation and discursive genre. It is expected that this research became a reference to Portuguese teachers, educators in general, and researchers who work in this area of study. Keywords: Bakhtin; textbook; dialogue; genre.